Losing As and Fs: What works for schools implementing standards-based grading? - Matt Townsley; Tom Buckmiller (Educational Considerations, 2020)
Learning goals such as the Common Core State Standards are helping educational leaders to better understand the critical role assessment and grading plays in the teaching and learning process. In response to the growing body of empirical research on the topic of accurate grading practices, a number of schools are moving away from letter grades and adopting standards-based grading which separately report learning goals from work habits. The purpose of this essay is to document what works when K-12 schools implement standards-based grading through a deep dive into related literature and to suggest areas for future consideration. With this improvement to educational systems on the horizon, K-12 teachers and administrators in the early stages of redesigning their grading practices will benefit from understanding the successes and struggles of early adopters in order to successfully reform grading in their own context.
Keywords: standards-based grading; educational leadership; assessment; grading; Common Core